2009
DOI: 10.2320/matertrans.m2009213
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ti-Ni-Zr Shape Memory Alloy by P/M Process

Abstract: This work focuses on the fabrication of Ti-Ni-Zr high-temperature shape memory alloy by powder metallurgy (P/M) process. The effects of fabrication conditions on the microstructure and shape memory characteristics of Ti-50.2 mol%Ni-5 mol%Zr alloy were investigated. In this research, elemental Ti, Ni and Zr powders were used. These powders were mixed by a planetary ball mill at a rotational speed of 500 rpm for milling times of 0.6 ks (mixed powder) and 720 ks (MAed powder). The mixtures were sintered by a puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…While Ti atoms migrate to form TiO 2 and TiO particles, residual Ni atoms diffuse into the TiNi matrix to form Ni-rich regions, and then the Ni 4 Ti 3 (223) and Ni 10 Zr 7 (422) phases appear 18,19 . Also in the N5 and N10 alloys, other phases appear, e.g., λ1 and NiZr phases and the coexistence of the austenite and martensite phases, which was also found by other authors 19,20 . Table 2 shows the transformation temperatures of these alloys.…”
Section: Resultssupporting
confidence: 81%
“…While Ti atoms migrate to form TiO 2 and TiO particles, residual Ni atoms diffuse into the TiNi matrix to form Ni-rich regions, and then the Ni 4 Ti 3 (223) and Ni 10 Zr 7 (422) phases appear 18,19 . Also in the N5 and N10 alloys, other phases appear, e.g., λ1 and NiZr phases and the coexistence of the austenite and martensite phases, which was also found by other authors 19,20 . Table 2 shows the transformation temperatures of these alloys.…”
Section: Resultssupporting
confidence: 81%
“…We have synthesized NPs of an ordered alloy (intermetallic compound) of an early d -metal and Pt, ZrPt 3 (ZrPt 3 NPs), and tailored their bulk structure by controlled annealing. It is known that the bulk structure of Zr-based alloys is sensitive to external stimuli such as pressure or temperature, often exhibiting shape-memory effects . We have demonstrated that a temperature-induced structural transformation in the ZrPt 3 NPs from cubic to hexagonal structures lowers the bulk free energy and, in turn, elevates the surface energy.…”
Section: Introductionmentioning
confidence: 80%
“…It is known that the bulk structure of Zrbased alloys is sensitive to external stimuli such as pressure or temperature, often exhibiting shape-memory effects. 28 We have demonstrated that a temperature-induced structural transformation in the ZrPt 3 NPs from cubic to hexagonal structures lowers the bulk free energy and, in turn, elevates the surface energy. The catalytic activity and stability of the ZrPt 3 NPs are significantly enhanced through the structural transformation, as the result of the elevated surface energy and the lowered bulk free energy.…”
Section: Introductionmentioning
confidence: 86%
“…Current HTSMAs systems include Cu-based alloys, NiAl, NiTi-based alloys (NiTiHf, NiTiZr, NiTiPd, etc.) [1][2][3][4][5][6][7], but until now some problems have remain unresolved. The brittleness of NiTiZr and NiTiHf limits their practical use [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7], but until now some problems have remain unresolved. The brittleness of NiTiZr and NiTiHf limits their practical use [1,2]. NiAl and Cu-based HTSMAs are considered unstable [4,5] because of precipitate phase formed at high temperature, which are detrimental to the shape memory effect.…”
Section: Introductionmentioning
confidence: 99%